Physical Fitness Attenuates the Impact of Higher Body Mass and Adiposity on Inflammation in Women With Systemic Lupus Erythematosus - Sola-Rodríguez, Sergio; Vargas-Hitos, José Antonio; Gavilán-Carrera, Blanca; Rosales-Castillo, Antonio; Ríos-Fernández, Raquel; Sabio, José Mario; Soriano-Maldonado, Alberto (Frontiers in Immunology, 2021)
Aims: Higher body mass and adiposity represent independent contributors to the systemic low-grade inflammatory state often observed in systemic lupus erythematosus (SLE). This cross-sectional study assessed the role of physical fitness in the association of body mass and adiposity with inflammation in women with SLE. Methods: A total of 77 women with SLE were included. We assessed body mass index, waist-to-height ratio, and body fat percentage as indicators of body mass and adiposity. Inflammation was assessed through plasma levels of C-reactive protein, interleukin 6, and leptin. Cardiorespiratory fitness was assessed through the 6-minute walk test, range of motion through the back-scratch test, and muscular strength with handgrip dynamometry. Results: Cardiorespiratory fitness attenuated the association of body mass index with interleukin 6 and the association of body fat percentage with interleukin 6 (all, P<0.05). Range of motion attenuated the association of body mass index with interleukin 6 (P<0.05) and the association of body fat percentage with C-reactive protein (P<0.05). These interactions indicated that higher fitness was associated with a lower increase in inflammation per unit increase body mass or adiposity. Muscular strength showed a non-significant trend to attenuate the association of body fat percentage with interleukin 6 (P=0.057) but potentiated the association of body fat percentage with leptin (P<0.05). Conclusion: These findings suggest that higher levels of cardiorespiratory fitness and range of motion might attenuate the impact of higher body mass and adiposity on inflammation in women with SLE. The role of muscular strength requires further investigation.